2015
DOI: 10.11646/zootaxa.3962.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Revalidation and redescription of Brachymystax tsinlingensis Li, 1966 (Salmoniformes: Salmonidae) from China

Abstract: Brachymystax tsinlingensis Li, 1966 is revalidated and redescribed. It can be distinguished from all congeners by the following combination of characteristics: no spots on operculum; gill rakers 15-20; lateral-line scales 98-116; pyloric caeca 60-71. Unique morphological characters and genetic divergence of this species are discussed. This species has a limited distribution in several streams of the middle part of the Qinling Mountains in China. Methods for management and protection of B. tsinlingensis need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
0
23
1
Order By: Relevance
“…For H. taimen and Brachymystax spp., haplotypes were labeled following Froufe, Alekseyev et al (); Figure c) and Froufe et al (; Figure ), respectively, using new names as necessary. In the analysis of Brachymystax, we also included GenBank sequences of B. tsinglingensis from China (Liu, Li, Lui, Zou, & Wei, ; Xing et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For H. taimen and Brachymystax spp., haplotypes were labeled following Froufe, Alekseyev et al (); Figure c) and Froufe et al (; Figure ), respectively, using new names as necessary. In the analysis of Brachymystax, we also included GenBank sequences of B. tsinglingensis from China (Liu, Li, Lui, Zou, & Wei, ; Xing et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Brachymystax genus is made up of three recognized species with two of these residing in Mongolia including B. lenok (sharp‐snouted lenok), the most widely distributed and commonly captured species (Kaus, ) and B. tumensis (blunt‐snouted lenok), a similar looking species which is found in more fragmented populations in the Onon River (Amur River Basin) (Bogutskaya & Naseka, ; Ma et al, ; Froufe, Alekseyev, Alexandrino, & Weiss, ; Xing et al, ). To date, both broad‐scale phylogroups and intrabasin genetic structuring have been identified for B. lenok between the major river basins across northern Asia/Siberia and within Chinese rivers, respectively (Froufe et al, ; Maric et al, ; Xia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some geological events also contributed to the formation of endemism. For example, the cold-water Brachymystax tsinlingensis is restricted to streams in the mid-Qinling Mountains, a consequence of the Last Glacial Maximum (Zhao & Zhang, 2009b;Xing et al, 2015). This kind of species is particularly susceptible to environmental impact.…”
Section: Comparison With Freshwater Fish Diversity Of Major River Basmentioning
confidence: 99%
“…Previous research on B. lenok has focused on phylogenetic origins of conspecifics (Froufe, Alekseyev, Alexandrino, & Weiss, 2008;Froufe, Alekseyev, Knizhin, Alexandrino, & Weiss, 2003;Shed'ko et al, 1996), spawning behaviour (Esteve & McLennan, 2008), feeding and diet (Chandra et al, 2005), thermal ecology (Hartman & Jensen, 2017) and biometric comparisons between lotic and lentic populations (Tsogtsaikhan et al, 2017). However, a detailed knowledge of this species' spatial ecology remains largely unknown, with only a single study being conducted on the re-described Brachymystax tsinlingensis Li 1966 (Xing et al, 2015) reported as B. lenok tsinlingensis in the Nakdong River, South Korea. In that study, the spring and winter movements and habitat utilisation of 51 individuals were monitored over multiple years, with the maximum home range detected for a mature individual being 8.17 km in spring and 4.13 km in winter (Yoon et al, 2015).…”
mentioning
confidence: 99%